(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Socio-economic development is the process of social and economic development in a society. Its purpose is to maintain the social and material well-being of the nation and its people with the aim of achieving the highest possible level of human development.